NIR-II absorptive dithienopyrrole-thiadiazolobenzotriazole conjugated polymer for photoacoustic imaging-guided glioblastoma multiforme photothermal therapy. (15th October 2022) - He, Yichen; Pan, Yi; Zhao, Xin; Fan, Weijiao; Cai, Yu; Mou, Xiaozhou
Abstract: The development of new diagnostic imaging and precise treatment methods for glioblastoma multiforme (GBM) is significant to improve patients' quality of life and prolong their survival time. Herein, we proposed a photoacoustic imaging (PAI)-guided GBM high-efficient photothermal therapy (PTT) based on a second near-infrared (NIR-II) absorptive polymer (PDTP-TBZ) conjugated with intense electron donor dithienopyrrole (DTP) and strong electron acceptor thiadiazolobenzotriazole (TBZ). By nanoprecipitation, PDTP-TBZ can form into nanoparticles (PT NPs), and c(RGDfK) cyclic peptide with integrin-specific targeting was then modified on the surface of PT NPs to obtain the ability of active targeting GBM multifunctional nano-reagent (cRGD@PT NPs). Both in vitro and in vivo experiments demonstrated that cRGD@PT NPs as NIR-II GBM phototheranostic reagents can greatly improve the enrichment rate at tumor sites under PAI monitoring, and carry out precise NIR-II PTT with high effective tumor cell phototoxicity and high biological safety. Thus, cRGD@PT NPs have great potential for the future GBM phototheranostic application in clinic. Statement of significance: In this work, we successfully constructed an intense electron donor dithienopyrrole (DTP) with a strong electron acceptor thiadiazolobenzotriazole (TBZ) into a novel NIR-II optical absorptive conjugated polymer (PDTP-TBZ). Then, the c(RGDfK) cyclic peptide was modified on the surface of PT NPs to obtain multifunctional nanodiagnostic reagents (cRGD@PT NPs) that can effectively target GBM neovascularization and tumor cells. Both in vitro and in vivo experiments demonstrate that cRGD@PT NPs possess high photothermal conversion efficiency and practical photoacoustic imaging capability under 1064 nm laser irradiation. The results of this work suggested that cRGD@PT NPs have great potential in efficient NIR-II PTT guided by accurate PAI, which provide a good perspective for the treatment and diagnosis of GBM. Graphical abstract: Image, graphical abstract